Chemical treatment of wastewater from palm oil mill effluent (POME) in cooperate with biodiesel production - Chin, Siaw Yin (Universiti Malaysia Sarawak (UNIMAS), 2013)
(The international demand for oil palm (Elaeis guineensis) is increasing, which lead to the rapid growth of palm oil industry in Malaysia. However, the industry is facing the challenge of sustainable water management due to large volume of water is used in the palm oil mill for the oil extraction process and increase of production of wastewater which is known as palm oil mill effluent (POME). This study detennines the POME water quality prior and after the POME is used to produce biodiesel. Indeed, further chemical treatment was used in order to obtain a better water quality. The objective of treating the POME is to reuse or recycle the water in the mill plant for example in the cooling process. Thus, the findings from this study helps to reduce freshwater consumption of the palm oil plant and minimum oil residue in the POME before it discharge to the receiving environmental bodies. Besides pollution prevention of the river, wastewater recycling within industry is also a resource recovery which helps reduce wastewater generation and save the production cost of the industry. In this study, POME was treated by de-oil process (biodiesel production) and the residual wastewater was treated with Fenton and photo-Fenton process, which COD reduction show high efficiency, which were 89.36% reduction through Fenton and 90.78% through photoFenton process.